Ethics, Error, and Initial Trials of Efficacy - Hey, Spencer Phillips (Sci Transl Med, 2013)
Concerns about the frequency of failure in late stage drug development have prompted a series of proposals for improving the positive predictivity of trials where clinical activity is first evaluated—typically phase 2 trials. However, many proposed reforms entail ethical and social tradeoffs that might not be immediately apparent. We argue that trial reforms aimed at boosting phase 2 positive predictivity have important repercussions for human subjects, as well as the capacity of the research enterprise to discharge its social mission. We articulate four factors that should guide the level of positive predictivity sought in middle stages of drug development: (1) clinical equipoise and the frequency with which new interventions are successfully translated in a given research area; (2) abundance of other candidates in a drug development pipeline; (3) the vulnerability of populations enrolled in middle stages of drug development; and (4) the social utility of negative phase 3 trials.